PROBLEM-BASED LEARNING (Konsep Ideal Model Pembelajaran untuk Peningkatan Prestasi Belajar dan Motivasi Berprestasi) - Esti Zaduqisti (Jurnal Forum Tarbiyah, 2010)
As the development of age into the era of globalization, allthe problems on this planet turns increasingly complex, innovativeand transparent. People who are not creative, and innovative absolutelywill be left behind by the rapid flow of these developments. Thesame case takes place in education, particularly in the learning process,in which there are many learning models emerging for the purpose ofprogress and success in learning. One such model is the ProblemBased Learning or often referred to as PBL (Problem BasedLearning) with an which is innovatively pictured by effective conceptin improving learners’ learning achievement and increasingachievemnt motivation of learners as well.